2013
DOI: 10.1038/sc.2013.71
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of oxidative stress on the prescription of rehabilitation interventions in spinal cord injury

Abstract: Study design: Review article. Objectives: To provide an overview of free radical biology, particularly with respect to muscle physiology, as well as the potential effects of muscle morphological changes, physical capacity and nutritional status on oxidative stress in people with chronic spinal cord injury (SCI). The potential implications of these factors for determining the optimal dosage of rehabilitation training interventions in people with chronic SCI will also be presented. Setting: Vancouver, BC, Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Oxidative stress is a series of adaptive reactions caused by the dysequilibrium between reactive oxygen in the body and the antioxidant system and, due to its importance in secondary injury in SCI, it has received increasing attention (3). Lam et al reported that the potential confounding effects of oxidative stress improved maximize functional recovery following SCI (4), and Ordonez et al found that arm-cranking exercises improved chronic spinal cord injury through the downregulation of oxidative damage (5).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a series of adaptive reactions caused by the dysequilibrium between reactive oxygen in the body and the antioxidant system and, due to its importance in secondary injury in SCI, it has received increasing attention (3). Lam et al reported that the potential confounding effects of oxidative stress improved maximize functional recovery following SCI (4), and Ordonez et al found that arm-cranking exercises improved chronic spinal cord injury through the downregulation of oxidative damage (5).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much attention has been focused on oxidative stress cascade leading to secondary injury after SCI because inhibition of the deleterious effects of it is thought to be one of the main mechanisms of therapeutic interventions [ 87 ]. ROS and RNS are the free radicals which cause devastating effects in biological system [ 88 ]. Recently it has been shown that MDA content significantly increased at 1 day after injury and reached a peak value at 7 days in the SCI group and SOD activity was significantly reduced in the SCI group at 1 day.…”
Section: Neuroprotective Role Of Melatonin In Scimentioning
confidence: 99%
“…Oxidative stress following the spinal cord injury is a main cause of secondary damages to neurons [ 1 3 ]. The levels of different reactive oxygen species (ROS), i.e.…”
Section: Introductionmentioning
confidence: 99%